Long-term stability of nickel-based ohmic contacts with n-type and p-type 4H-SiC in a high-temperature environment. (8th October 2020) - Masunaga, Masahiro; Crescitelli, Viviana; Funaki, Tsuyoshi
Abstract: Long-term thermal stability of specific contact resistance ( ρ c ) in cross-bridge Kelvin resistors (CBKRs), with an Al/TiN/Ti/Ni2 Si/4H-SiC layered structure, was studied. In high-temperature-storage tests at 500 °C, ρ c of p-type SiC increased after it decreased to 1/100 from its initial value; however, in high-temperature-storage tests at 300 °C, it was stable up to 1000 h. The initial decline of ρ c was due to the formation of titanium–silicide alloy, whose barrier height is lower than that of the Ni2 Si phase. It was found that ρ c increased when the aluminum electrode disappeared because aluminum displaced silicon in the silicon-dioxide layer. In thermal-shock tests (−40 °C/300 °C), ρ c hardly changed up to 2000 cycles, and that trend was constant regardless of SiC carrier type. In both tests, almost no thermal deterioration of ρ c around 300 °C was observed even in air, so it is concluded that the CBKR structure is robust enough for installation in a high-temperature environment such as a nuclear power plant under decommissioning.